Peningkatan Penjualan Kopi Bubuk Melalui Program Repackaging di Dusun Stabelan Kabupaten Boyolali - Novria Prawida; Wahyudhi Sutrisno; Wahyu Ismail; Atyanti Dyah Prabaswari (Universitas Islam Indonesia, 2023)
Arabica coffee, a specialty of Stabelan Hamlet, Boyolali Regency, is produced by Stabelan Coffee Production House. Observations show that many visitors enjoy the flavor of Stabelan Arabica Coffee. Unfortunately, they don't buy coffee to take home as mementos; they just buy it to drink there and then. This is because Stabelan Ground Coffee's packaging, which simply employs plain white paper, makes it unsuitable for souvenirs. Therefore, it is essential to perform community service in order to modify the packaging for Stabelan ground coffee in order to entice travelers to purchase it. The packaging must reflect the caliber of the coffee while also introducing Stabelan Hamlet to possible new tourists.. Based on consultation and discussions with the community, new packaging will be created to match Stabelan coffee powder. The new packaging is a stand-up pouch featuring the iconic Stabelan Hamlet image. The stand-up pouch was chosen because it is practical, affordable, available in different sizes, looks modern and attractive, and the quality of the coffee is guaranteed in terms of shape, taste and aroma. The new packaging is expected to increase sales of Stavelan ground coffee.